Guia Tecnica Para La Obtención De Leche De Calidad A Nivel De Ganadería (2024)
Milk is characterized by being a food of high nutritional value, providing the world population with vitamins, minerals and protein substances, among others. Its origin is generally found in ruminant species such as cattle, goats and buffaloes, however, bovine milk is the one that demands greater consumption. For milk production, year after year different health standards and procurement guidelines are stipulated with appropriate safety protocols, in order to obtain a product.